2006
DOI: 10.1590/s0101-81752006000100015
|View full text |Cite
|
Sign up to set email alerts
|

Padrão de deslocamento do camarão marinho Litopenaeus vannamei (Boone) (Crustacea, Decapoda, Penaeidae) nas fases clara e escura ao longo de 24 horas

Abstract: O padrão diário de atividade de Litopenaeus vannamei (Boone, 1931) (Crustacea, Decapoda, Penaeidae) é ainda pouco entendido. Com o objetivo de fornecer subsídios para otimizar o manejo nas fazendas de cultivo através do estudo do comportamento deste animal, foram desenvolvidos experimentos com juvenis (7,57 ± 1,01 g), mantidos em aquários (30 l). Para registro da atividade, os aquários foram submetidos a fotoperíodo artificial (fase do claro e do escuro, 12h:12 h), sendo monitorados 16 camarões (33 m²) em cada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…Pesquisas em etologia aplicada têm como objetivo principal o entendimento e a promoção desse bem-estar, o que tem sido uma preocupação da sociedade contemporânea, confirmada pela criação da "International Society for Applied Ethology" (Isae) (Millman et al, 2004). No entanto, ainda são necessárias informações sobre o comportamento dos camarões em cativeiro, o que inclui a fase clara e escura do ciclo de 24 horas (Pontes, 2006;Lima et al, 2009).…”
Section: Introductionunclassified
“…Pesquisas em etologia aplicada têm como objetivo principal o entendimento e a promoção desse bem-estar, o que tem sido uma preocupação da sociedade contemporânea, confirmada pela criação da "International Society for Applied Ethology" (Isae) (Millman et al, 2004). No entanto, ainda são necessárias informações sobre o comportamento dos camarões em cativeiro, o que inclui a fase clara e escura do ciclo de 24 horas (Pontes, 2006;Lima et al, 2009).…”
Section: Introductionunclassified
“…According to Pontes and Arruda (2005) and Pontes (2006), who studied the behavior and displacement pattern of L. vannamei during light and dark periods, laboratory observations indicated that certain species of Penaeidae are much more active at night and thus more vulnerable to net capture. Hence, the results for P. muelleri obtained by the current study are consistent with those previously observed for members of the Penaeidae because 70% of the P. muelleri individuals were captured at night.…”
Section: Discussionmentioning
confidence: 99%
“…The collections at night constituted 66.4% of the total captures. Pontes (2006) investigated the displacement pattern of juvenile shrimp Litopenaeus vannamei (Boone, 1931) submitted to artificial photoperiodic conditions and observed that this displacement occurs primarily during the dark phase. This observation is consistent with the finding that the greatest activity of this species occurs during the dark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results on behavioural and feeding activities as a function of feed offer suggest that feed must be offered in the light phase and at a greater proportion 7 h after sunrise (Pontes & Arruda 2005b; Pontes, Arruda, Menezes & Lima 2006). Substrate exploration behaviour, indicative of the search for feed, was more intense around this time (Pontes 2006).…”
Section: Discussionmentioning
confidence: 99%